The Role of Islamic Religious Education in Growing a Sense of Nationalism - Devita Wahyu Azhar; Warlina Febrita Putri; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
A sense of nationalism to the homeland is _ something Thing urgent for achieving the Indonesian goals that have been listed on Opening Invite Invite base year 1945. This is in line with Islamic teachings. Where is the religion of Islam? honor, as well as respect high love _ to homeland or _ love to nationality as nature sure man _, owned. Factors that give impact a sense of nationalism there is two, namely internal factors and factors external. Two factors this is the reason for growing or not a sense of nationalism to the homeland or _ country. To add love _ to the homeland on _ self child young especially on student-student sitting on the bench school conducted application that grows and develops values and a sense of nationalism. Where are things implemented in the learning process teaching?